2012
DOI: 10.11648/j.am.20120101.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Titanium Carbide on the Three- Body Abrasive Wear Behaviour of Glass-Fabric Reinforced Epoxy Composites

Abstract: Abstract:The three-body abrasive wear of Titanium Carbide (TiC) filled and unfilled E-glass-epoxy (G-E) was experimentally investigated using rubber wheel abrasion tester (RWAT). The composites were fabricated by using vacuum assisted resin transfer molding (VARTM) with 0-6 wt % of TiC in steps of 2 wt %. The mechanical properties of the TiC filled and unfilled glass fabric reinforced epoxy (G-E) composites have been evaluated. From the experimental results, it is observed that the mechanical properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…However, it decreases sharply with changing the FL from 3 to 4.5 wt.%. Whereas, with an increment in filler stacking from 1.5 to 4.5 wt.%, there is a decrease in the SWR because as the nano-CaCO3 stacking builds, the quantity of nano-CaCO3 filler particles in the transfer film additionally increments, and it causes the interruption of transfer film because of the more number of hard particles [50].…”
Section: Analysis Of Wear Results Of Nano-caco3 Filled Hybrid Compositesmentioning
confidence: 99%
“…However, it decreases sharply with changing the FL from 3 to 4.5 wt.%. Whereas, with an increment in filler stacking from 1.5 to 4.5 wt.%, there is a decrease in the SWR because as the nano-CaCO3 stacking builds, the quantity of nano-CaCO3 filler particles in the transfer film additionally increments, and it causes the interruption of transfer film because of the more number of hard particles [50].…”
Section: Analysis Of Wear Results Of Nano-caco3 Filled Hybrid Compositesmentioning
confidence: 99%
“…The contributions of T, L and S were about 33.55, 24.54 and 21.87 %, respectively. However, sliding/abrasive distance was the wear factor that had the highest statistical influence on the dry wear of composites [22,33,35].…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 99%
“…For all tested polymers like POM, UHMWPE, PA66 and its composites, the wear rate increased linearly with abrasive distance and grit sizes. Several other studies indicated that Taguchi approach was applied on the abrasive wear behavior of the polymeric materials including glass/carbon fibers/fabrics and SiC particles [27][28][29][30][31][32][35][36][37][38][39][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the abrasive wear behaviour, several key parameters such as modifying tribo-system, replacing metal surface with plastic or ceramic one, optimising testing parameters, changing environment, and proper material's selection should be considered (Franklin, 2001;Schwartz and Bahadur, 2001). There have been a quite numbers of investigations on effects of testing conditions, particle size, contact geometry, role of filler and environment on adhesive wear behaviour (Hooke et al, 1996;Khedkar et al, 2002;Wang and Li, 1999) and abrasive wear behaviour of polymers (Anand and Kumaresha, 2012;Chand and Dwivedi, 2007;Unal et al, 2005), and its composites (Rao, 2013;Raju et al, 2012;. Bijwe et al (1989) have tested polyamide 6, polytetrafluoroethylene and their various composites in abrasive wear under multipass conditions.…”
Section: Introductionmentioning
confidence: 99%